Atalaia Catholica, Jornal Religioso. (Typographia Luzitana, 1855)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Sermões do padre Antonio Vieira - António Vieira (J.M.C. Seabra & T.Q. Antunes, 1855)
Keywords: OBRAS DO PADRE ANTONIO VIEIRA; Religion

The Spanish conquest in america and its relation to the history of slavery and to the government of colonies - Arthur Helps (John W. Parker and son west strand, 1855)
Keywords: 18.Bookworm; 22.signature; 22.stamp; 28.Iron-gall ink; Condition: Fair; Hard Cover; History

Oeurves Spirituelles de S. Bonaventure - Berthaumier, M. L'abbe (Louis vives, Libraire-Editeur, 1855)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Oeuvres Spirituelles de S. Bonaventure - Berthaumier, M. L'abbe (Louis vives, Libraire-Editeur, 1855)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Cyclopædia of English literature: a selection of the choicest productions of English authors, from the earliest to the present time, connected by a critical and biographical history - Chambers, Robert (Gould, Kendall and Lincoln, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 8.Tear; Condition: Poor; Dictionaries; English literature; English literature Dictionaries; Hard Cover

Cyclopædia of English literature: a selection of the choicest productions of English authors, from the earliest to the present time, connected by a critical and biographical history - Chambers, Robert (Gould, Kendall and Lincoln, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 8.Tear; Condition: Poor; Dictionaries; English literature; English literature Dictionaries; Hard Cover

Considerations sur les Principlaes Actions du Chretien - Crassset, R. P. Jean (Charles Douniol, Libraire, 1855)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exposition et histoire des principales découvertes scientifiques modernes - Figuier, Louis (Langlois et Leclercq, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Découvertes scientifiques; Hard Cover; History; Industrial arts; Industrial arts History; Inventions; Métiers Histoire

Exposition et histoire des principales découvertes scientifiques modernes - Figuier, Louis (Langlois et Leclercq, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Découvertes scientifiques; Hard Cover; History; Industrial arts; Industrial arts History; Inventions; Métiers Histoire

Exposition et histoire des principales découvertes scientifiques modernes - Figuier, Louis (Langlois et Leclercq, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; Condition: Fair; Découvertes scientifiques; Hard Cover; History; Industrial arts; Industrial arts History; Inventions; Métiers Histoire

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 2.Damage; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; 2.Damage; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; Fair

Nouveau Commentaire, Litteral, Critique et Theologique - Gimarey, M. L'Abbe. (Chez Louis Vives., 1855)
St. Joseph Seminary's Stamp
Keywords: 18.Bookworm; Fair

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Historiarum Libri, T. Livii Patavini - Livy, Titus (Typis Academicis, 1855)

Fastos da Igreja Historia da Vida Dos Santos, Ornamentos do Christianismo - Luiz Augusto Rebello da Silva (Em casa de A. J. F . Lopes, 1855)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 2.Damage

Explication des Premieres Verites de La Religion - M. P. C. (Perisse Freres, Imprimeurs- Libraires, 1855)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Arte de furtar, espelho de enganos, theatro de verdades, mostrador de horas minguadas, gazúa geral dos reinos de Portugal: Offerecida a el-rei nosso senhor D. João IV para que a emende - padre antonio vieira (Obras politicas e varias, 1855)
Keywords: 10.Cover Damage; 16.Waterstains; 2.Damage; 22.signature; Condition: Poor; Fraud; Fraude; Hard Cover; Politics and government; Portugal; Portugal Politics and government; Portugal Politique et gouvernement; Swindlers and swindling; fraud

De Immaculato Deiparae Semper Virgeinis - Passaglia, Caroli (1855)
Keywords: 2.Damage

Pratique de la Perfection Chretienne et Religieuse - Rodriguez, R. P. Alphonse (Im. Lib. Perisse Freres, 1855)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Fatos da Igreja Historia da Vida dos Santos - Silva, Luiz Augusto Rebello (Em casa de A. J. F . Lopes, 1855)
Stamp, Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage

Fatos da Igreja Historia da Vida dos Santos - Silva, Luiz Augusto Rebello (Em casa de A. J. F . Lopes, 1855)
Stamp, Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage

historiarum libri, qui supersunt, cum deperditorum fragmentis - t. livii patavini (Typis Academicis, 1855)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; History

Sermões do padre Antonio Vieira - Vieira, António (J.M.C. Seabra & T.Q. Antunes, 1855)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; 8.Tear; Catholic Church; Catholic Church Sermons; Condition: Poor; Hard Cover; Oratoria portuguesa; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Sermões do padre Antonio Vieira - Vieira, António (J.M.C. Seabra & T.Q. Antunes, 1855)
Keywords: 10.Cover Damage; 14.missing area; 16.Waterstains; 18.Bookworm; 2.Damage; 22.signature; 28.Iron-gall ink; Catholic Church; Catholic Church Sermons; Condition: Poor; Hard Cover; Oratoria portuguesa; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Sermões do padre Antonio Vieira - Vieira, António (J.M.C. Seabra & T.Q. Antunes, 1855)
Keywords: 10.Cover Damage; 13.Page missing; 16.Waterstains; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Poor; Hard Cover; Oratoria portuguesa; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons